Limits on the real line of symmetric spaces on segments - Kucher О. V.; Plichko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
In the same way as the known spacesM p ,M p , andI p are constructed on the basis of the spaceL p (−1, 1), we construct the corresponding “limit” spacesM E ,M E , andI E on the real line on the basis of a symmetric function spaceE on a segment and study some of their Banach properties.